2015
DOI: 10.1177/1077801215596849
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Telephone Support Services to Prevent Further Intimate Partner Violence

Abstract: We conducted a randomized-controlled trial of telephone support services (TSS) versus enhanced usual care (EUC) for women who had reported intimate partner violence (IPV) within the past year during a visit to a pediatric emergency department. TSS nurse interventionists identified appropriate referrals to community programs, helped participants by problem-solving barriers to obtaining these local services, and provided social support. Three hundred women, ages 18 years and above were recruited. The TSS and EUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…Krasnoff and Moscati's study [51] discussed a multi-component referral, support and case management intervention that reported similar reduction in perceived IPV victimization as seen in studies included in our review. There were some differences in the telephone support interventions included, Stevens et al's study [27] reported no difference in mental health outcomes compared to Tiwari et al's study [15] which found an improvement in mental health outcomes among the intervention group. We postulate differences in outcome could be attributable to the fact that Tiwari's intervention was more advocacy, empowerment and support focused than the intervention described in Stevens et al study, which was more information and referral focused.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Krasnoff and Moscati's study [51] discussed a multi-component referral, support and case management intervention that reported similar reduction in perceived IPV victimization as seen in studies included in our review. There were some differences in the telephone support interventions included, Stevens et al's study [27] reported no difference in mental health outcomes compared to Tiwari et al's study [15] which found an improvement in mental health outcomes among the intervention group. We postulate differences in outcome could be attributable to the fact that Tiwari's intervention was more advocacy, empowerment and support focused than the intervention described in Stevens et al study, which was more information and referral focused.…”
Section: Discussionmentioning
confidence: 94%
“…These interventions involved the use of community-based advocacy interventions focused on individuals that were survivors of violence, these interventions were focused on assisting the survivors identify and access resources, supportive relationships and cope with the effects of intimate partner violence. Fifteen of the studies reviewed (11 RCTs, 2 pre-post evaluation, 1 retrospective study, 1 quasi-experimental study with randomization) described experiences with social support interventions that provided some sort of advocacy service in combination with community support for survivors of violence, on an individual level [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Advocacy/ Case Management Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…M. Sullivan & Davidson, 1991; C. M. Sullivan, Tan, Basta, Rumptz, & Davidson, 1992; Tiwari et al, 2005, 2010) and 8 were individual-level clinically focused interventions (Gilbert et al, 2016; Iverson et al, 2011; Kiely et al, 2010; Miller et al, 2014; Rhodes et al, 2015; Stevens et al, 2015; Weir et al, 2009; Zlotnick et al, 2011). One intervention provided a community-based mutual aid support group which was clinically focused (Tutty et al, 1993), one intervention was a shelter-based intervention providing both a mix of clinical and advocacy services (McNamara et al, 1997), and two were a mixed individual and group clinical interventions.…”
Section: Resultsmentioning
confidence: 99%
“…58,59 High-risk breast cancer assessment included seven studies comparing in-person to telegenetic counseling, [60][61][62][63][64][65][66] and two addressing the needs of women at high risk. 67,68 IPV included six studies that promoted the safety or well-being of women who had experienced IPV, [69][70][71][72][73][74] and one study addressed post-exposure HIV prophylaxis. 75 There was one SR that examined telephone interventions for preventing new HIV infection 76 that identified this same study.…”
Section: Primary Studies and Systematic Reviewsmentioning
confidence: 99%